Pengaruh Customer Experience, Service Quality, dan Perceived Value Terhadap Customer Loyalty Dimediasi Oleh Customer Satisfaction - Yulia Citra; Ketut Sunaryanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation through e-commerce has changed consumer preferences in purchasing beauty and cosmetic products online. However, the existence of offline stores remains relevant because it can provide an irreplaceable virtual shopping experience. This study aims to analyze the influence of Customer Experience, Service Quality, and Perceived Value on Customer Loyalty with Customer Satisfaction as a mediating variable. The approach used is a quantitative approach with the SEM-PLS data analysis method. The study population was customers of offline beauty and cosmetic stores in malls in the Greater Jakarta area. Data were obtained through distributing questionnaires via google forms and 115 respondents were analyzed using SEM-PLS. The results show that Customer Experience, Service Quality, and Perceived Value have a positive effect on Customer Satisfaction. In addition, Customer Satisfaction is proven to mediate the relationship between Customer Experience and Customer Loyalty. These findings provide a strategic contribution for beauty and cosmetic industry players, especially offline stores, that improving customer experience, service quality, and perceived value can shape customer loyalty. This study emphasizes the importance of optimizing the shopping experience as a competitive advantage in the digital era.